Faktor-Faktor yang Berhubungan dengan Partisipasi Ibu Menimbang Balita - Fara, Yetty Dwi; Fauziah, Nur Alfi; Rahmayani, Riana (Universitas Aisyah Pringsewu (UAP) Lampung, 2019)
Weighing is one of the main activities of the nutrition improvement program that focuses on preventing and improving on child nutrition condition. The government builds program in order to overcome these problems by making efforts to move the community through the development of village community health with an operational implementation as a form of Pos Pelayanan Terpadu (Posyandu). Coverage of weighing toddlers in Lampung province is 76.48% but has not met the target, East Lampung Health Office recorded that there was still a lack of weighing coverage of 74.32%, Posyandu Sukadana recorded 51.48%, and in Posyandu Cermai 3 by 43%. The purpose of this study is to find out the factors Associated with Maternal Participation for Weighing Toddler at Posyandu Cermai 3 in Rajabasa Batanghari Village 2018. The design used in this study is correlation with the cross sectional approach. The population in this study were all mothers who had toddlers 6-59 months at the Posyandu Cermai 3 in Rajabasa Btanghari Village in 2018 which numbered 128, while the sample taken was 96. Bivariate analysis in this study used Chi Square Test. The results of the study obtained p value 0,005 which means there is a relationship between education and maternal participation, p value 0.048 means that there is a relationship between work and maternal participation, p-value 0,079 means that there isn’t relationship between the parity and maternal participation at the Posyandu Cermai 3 in Rajabasa Batanghari Village 2018.